2021
DOI: 10.1111/ocr.12542
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of automatic cephalometric landmark identification using artificial intelligence

Abstract: Despite advances in orthodontic technology, including innovation(s) in imaging systems and software, the approaches used in diagnosis and treatment planning have not experienced similar advances during the past century. 1,2 For example, most clinicians use cephalometrics for orthodontic diagnosis and treatment planning. In 2002, 90% of orthodontists in the United States routinely obtained

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 16 publications
0
32
0
Order By: Relevance
“…It allows for automatic cephalometric point detection and tracing in seconds; however, the software requires that a lateral radiograph be obtained only on the Planmeca cephalometric imaging unit, where it is automatically calibrated, resized, and oriented [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It allows for automatic cephalometric point detection and tracing in seconds; however, the software requires that a lateral radiograph be obtained only on the Planmeca cephalometric imaging unit, where it is automatically calibrated, resized, and oriented [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Park et al (60,61) demonstrated a DL algorithm for the automatically identifying cephalometric landmarks on radiographs with a high accuracy. Bulatova (68) et al and Kunz et al (69) developed similar AI algorithms, with accuracies comparable with human examiners in identifying those landmarks. An automatic system for skeletal classification using lateral cephalometric radiographs was proposed by Yu et al (63).…”
Section: Ai In Orthodonticsmentioning
confidence: 99%
“…Moreover, various AI models have been utilized to classify the normal and osteoporotic subjects, aiming to assist physicians in identifying patients with osteoporosis before implant treatment [24]. In terms of the clinical decision making, the AI-based clinical decision support systems have been developed for the diagnosis of oral and maxillofacial pain [14], the analysis of teeth extraction strategy in orthodontic treatment [25], the automatic identification of the landmark points in cephalometric [26], and the design of removable partial denture in oral prostheses [27].…”
Section: Related Workmentioning
confidence: 99%